Does knowledge and concern regarding food supplement safety affect the behavioral intention of consumers? An experimental study on the theory of reasoned action - Bayır, Talha; Çam, Selim; Tuna, Murat Fatih (Frontiers in Nutrition, 2024)
In recent years, health crises have led consumers to make more frequent purchases of food supplements. The global food supplement market, which reached 61.20 billion in 2020, is estimated to reach 163.12 billion by 2022 and 350.96 billion by 2032. However, many consumers still have concerns about the safety of food supplements. Within the scope of the research, firstly, the health consciousness (HC) level of food supplement consumers was determined. Secondly, food safety knowledge (FSK) and food safety concerns (FSCs) were measured. Thirdly, consumers’ attitudes (ATUs), subjective norms (SNs), and behavioral intentions (BIs) toward food supplements were determined within the scope of the theory of reasoned action. The study used a convenient sampling, and 327 participants were included in the sample population. The data for the analysis was collected using the online survey method in the third quarter of 2023. The relationships between hypothesized items in the structural model were tested using the Smart-PLS. The validity and reliability of the measurement model were evaluated at the start of the structural equation modelling approach using confirmatory factor analysis (CFA). Regression analyses were performed in the structural model phase to evaluate overall fit and suggested relationships by way of the Smart-PLS. In light of the findings, it was determined that the interaction between HC and ATU was mediated by FSK, and the interaction between HC and the SN was mediated by FSK. Consequently, this research presents a variety of theoretical and practical implications to give clues for consumers’ health regarding food supplement consumption.